Perversion and Nonknowledge as Technique for Madness - Tim Themi (The European Journal of Psychoanalysis, 2023)
This article conjoins Lacan’s Seminar discussions of perversion with Bataille’s notion of nonknowledge at the core of being. It shows how Lacan’s critique of commonplace mis-readings of nonknowledge, likened to Talking to Brick Walls, reveals precisely psychoanalytic knowledge, of the polymorphous-perverse truth of jouissance, here at stake. It intervenes on Lacan’s linking of Bataille’s inner-experience, that “God is a whore,” to Schreber’s persecutory delusion, to restore eroticism to a technique for managing madness—one that involves an easing of the strictures of Western metaphysics.
Keywords: Lacan and Bataille; Freud and Nietzsche; epistemology; Neurosis; psychosis; perversion